The Role of Community Engagement in SME Management: A Qualitative Synthesis - Rumasukun, Mohammad Ridwan; Noch, Muhammad Yamin (Golden Ratio of Community Services and Dedication, 2023)
This research investigates the role of community engagement in Small and Medium Enterprises (SMEs) management. Utilizing a qualitative synthesis of literature, the study aims to explore various approaches, strategies, and implications of community engagement for SMEs. Through an in-depth analysis of existing research, including scholarly articles, books, and reports, the research elucidates the diverse methods employed by SMEs to engage with their communities, such as corporate social responsibility (CSR) initiatives, stakeholder partnerships, and participatory decision-making processes. The findings reveal that effective community engagement enables SMEs to access local resources, networks, and knowledge, thereby enhancing their competitiveness and resilience in the market. Additionally, community engagement fosters trust, goodwill, and social capital, leading to increased customer loyalty, positive reputation, and improved financial performance for SMEs. However, the research also identifies challenges and complexities associated with community engagement, including limited resources, cultural differences, and stakeholder dynamics. Moving forward, the study emphasizes the need for a multi-perspective approach to further explore and understand the mechanisms underlying community engagement in SME management. Practical implications include the importance of adopting context-specific strategies and building internal capacity for effective community engagement. The research contributes to advancing knowledge in the field of SME management by providing insights into the significance of community engagement for organizational success and sustainability.